NORMAL ULTRASONIC PARAMETERS OF AVARIES OF GIRLS FROM 13 YEARS TILL 23 - Kamalova Gulnara Gulyamovna; Qozoqova Ziyodaxon Turg`unovna (Scholar Express Journals, 2025)
On 380 ecogramms were inesigated by us echoparameters of avaries, which obtained from girls. The reseaches shoved, that the girls of 13 years till 23 the length of right avaries in before BMLO menstruation leftside avulation grows medium to 5,4 mm, left avaries-to 7,6 mm, in before menstruation BMRO rightside ovulation-properly: to 5,8 and 6,2 mm, frontback size is to 3,2 and 3,6 mm; to 2,7 and 3,6 mm; width-to 3,1 and 3,5 mm; to 3,5 and 2,8 mm and volume to 1,9 and 40 sm; to 1,7 and 1,9 sm. Ultrasonic dimensions of avaries on obtained ages during menstrual cycle changes heterochronny and heterodynamically.
Keywords: echoparametrs; ultrasonic; ovarium